Human papillomavirus testing versus cytology in primary cervical cancer screening: End‐of‐study and extended follow‐up results from the Canadian cervical cancer screening trial. Issue 11 (30th August 2016) - Isidean, Sandra D.; Mayrand, Marie‐Hélène; Ramanakumar, Agnihotram V.; Gilbert, Laura; Reid, Stephanie L.; Rodrigues, Isabel; Ferenczy, Alex; Ratnam, Sam; Coutlée, François; Franco, Eduardo L.; ,
Abstract : The Canadian Cervical Cancer Screening Trial was a randomized controlled trial comparing the performance of human papillomavirus (HPV) testing and Papanicolaou cytology to detect cervical intraepithelial neoplasia of grades 2 or worse (CIN2+) among women aged 30–69 years attending routine cervical cancer screening in Montreal and St. John's, Canada ( n = 10, 154). We examined screening and prognostic values of enrollment cytologic and HPV testing results. Extended follow‐up data were available for St. John's participants ( n = 5, 754; 501, 682.6 person‐months). HPV testing detected more CIN2+ than cytology during protocol‐defined (82.9 vs . 44.4%) and extended (54.2 vs . 19.3%) follow‐up periods, respectively. Three‐year risks ranged from 0.87% (95% CI: 0.37–2.05) for HPV‐/Pap‐ women to 35.77% (95% CI: 25.88–48.04) for HPV+/Pap+ women. Genotype‐specific risks ranged from 0.90% (95% CI: 0.40–2.01) to 43.84% (95% CI: 32.42–57.24) among HPV− and HPV16+ women, respectively, exceeding those associated with Pap+ or HPV+ results taken individually or jointly. Ten‐year risks ranged from 1.15% (95% CI: 0.60–2.19) for HPV−/Pap− women to 26.05% (95% CI: 15.34–42.13) for HPV+/Pap+ women and genotype‐specific risks ranged from 1.13% (95% CI: 0.59–2.14) to 32.78% (95% CI: 21.15–48.51) among women testing HPV− and HPV16+, respectively. Abnormal cytology stratified risks most meaningfully for HPV+ women. Primary HPV testing every 3 years provided a similar or greater level of reassurance against disease risks as currently recommended screening strategies. HPV‐based cervical screening may allow for greater disease detection than cytology‐based screening and permit safe extensions of screening intervals; genotype‐specific testing could provide further improvement in the positive predictive value of such screening. Abstract : What's new? Screening programs using Papanicolaou (Pap) cytology have revolutionized cervical cancer prevention worldwide but have been scrutinized for low sensitivity and costly infrastructure. Here the authors report the results of the Canadian Cervical Cancer Screening Trial, which compared Pap cytology with human papillomavirus (HPV) testing as screening strategies. Indeed, HPV testing detected more high‐grade cervical lesions and cervical cancer than cytology during protocol‐defined (82.9 vs. 44.4%) and extended (54.2 vs. 19.3%) follow‐up periods, respectively. Genotype‐specific testing was shown to further stratify risks among HPV+ women, which could provide further improvement in the value of HPV‐based screening. As the study was designed to satisfy stringent standards required for policy‐making, these findings will likely contribute to more efficient and effective cervical cancer screening strategies in Canada and elsewhere.